Licit and illicit substance use patterns among university students in Germany using cluster analysis - Schilling, Laura (Subst Abuse Treat Prev Policy, 2017)
BACKGROUND: The use of multiple licit and illicit substances plays an important role in many university students’ lives. Previous research on multiple substance use patterns of university students, however, often fails to examine use of different illicit substances and/or hookah. Our objective was to complement and advance the current knowledge about common consumption patterns regarding illicit substances and hookah use in this group. METHODS: Students from eight German universities completed an online survey as part of the INSIST study (‘INternet-based Social norms Intervention for the prevention of substance use among STudents’) regarding their consumption of alcohol, tobacco, hookah, cannabis and other illicit substances. Cluster analysis identified distinct consumption patterns of concurrent and non-concurrent substance use and multinomial logistic regressions described key sociodemographic factors associated with these clusters. RESULTS: Six homogeneous groups were identified: ‘Alcohol Abstainers’ (10.8%), ‘Drinkers Only’ (48.2%), ‘Drinkers and Cigarette Smokers’ (14.6%), ‘Cannabis and Licit Substance Users’ (11.2%), ‘Hookah Users with Co-Use’ (9.8%) and ‘Illicit Substance Users with Co-Use’ (5.4%). Illicit substance use clustered with the consumption of alcohol, tobacco and cannabis. Hookah use was regularly associated with alcohol consumption, less commonly associated with tobacco or cannabis use and very rarely associated with use of other illicit substances. Individuals consuming licit and illicit substances or hookah were mostly male and lived together with other students. Characteristics such as the number of years an individual had spent studying at a university, subject of study, immigrant background and religious affiliation were less commonly associated with cluster membership. CONCLUSIONS: Although we found substance use patterns in our sample largely similar to previous reports, we identified an important subgroup of individuals using both illicit and licit substances. These individuals may benefit especially from targeted interventions that focus on modifying addictive behavior patterns. TRIAL REGISTRATION: DRKS00007635. Registered 17 December 2014 (retrospectively registered).